A system to evaluate and monitor quality of life in an University Campus - Rodrigues, Daniel Souto (2005)
Usually considered as an urban space, a university campus is commonly planned and managed under this perspective. For that reason, the conceptualization of the university campi’s quality of life (QLU) should fit to the definitions established for this type of environment. Although it is recognized the difficulty to find a universal quality of life definition for urban environments, there is some consensus for the approach to its conceptualization. In this context, this paper presents a model to evaluate the quality of life for university campi. Related topics are discussed, such as the multicritera frame, the dimensions and indicators, and the data requirements. Furthermore, the methodology is applied to a case, which is the development of an accessibility map for the University of Minho campus.